Building Conservation Ranger Agent to Foster Mangrove Environmental Responsibility Using ABCD Approach - Sawiji, Asri; Yuliati, Dian (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
Mangrove forests have an enormous role to play in environmental sustainability. Environmental pollution, especially plastic garbage trapped in mangrove roots, will damage the ecosystem. Awareness of the preservation of the mangrove forest ecosystem requires education from an early age. The empowerment activity aims to provide support to elementary school students who are in the coastal area on knowledge of the mangrove forest ecosystem as well as the management of garbage with the 3R system (Reduce, Reuse, Recycle) in Surabaya. This adjacent uses the ABCD approach (Asset Based Community Development). The stages of this dedication are (1) discovery, (2) dream, (3) design, and (4) destiny. The ABCD method uses the assets that exist in the community to be better utilized in efforts to reach a shared vision. This community service program has provided benefits and had a positive impact on students. As a result of this community outreach, there has been a significant increase in students' knowledge of mangrove ecosystems and waste management with 3R systems. In addition, as many as 69% of students are willing to become mangrove forest conservation ranger and are committed to environmental sustainability.